2022
DOI: 10.3390/jcm11113195
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preserving Surgery Outcomes for Ovarian Malignancy: Data from a Tertiary Cancer Centre in Central London

Abstract: Fertility Sparing Surgery (FSS) appears to be a safe means of treating early-stage ovarian cancer based on relatively limited evidence. However, there is currently insufficient evidence to aid women in counselling about their potential fertility outcomes. The aim of this study was to assess the reproductive outcomes and prognosis of women who have undergone FSS for ovarian malignancy. Between 1 June 2008 and 1 June 2018, a retrospective review of a clinical database was conducted to identify all consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Similarly, Gaughran et al [10] conducted a study involving 36 patients and found a significant correlation between fertility-sparing surgery (FSS) and higher mortality rates for disease stage >1A (p = 0.02) and tumor grade >1 (p = 0.02). Disease recurrence was associated with disease stage >1A (p = 0.07) and the use of in vitro fertilization (IVF) (p = 0.03).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Gaughran et al [10] conducted a study involving 36 patients and found a significant correlation between fertility-sparing surgery (FSS) and higher mortality rates for disease stage >1A (p = 0.02) and tumor grade >1 (p = 0.02). Disease recurrence was associated with disease stage >1A (p = 0.07) and the use of in vitro fertilization (IVF) (p = 0.03).…”
Section: Discussionmentioning
confidence: 94%
“…Data regarding reproductive outcomes in patients with conservative treatment of ovarian cancer should be interpreted carefully and without generalization. Successful conception rates vary between 30 and 60% with a rate of abortion from 4 to 17% [54,56 && , [70][71][72]. Otherwise, obstetrical outcomes (rate of malformation, miscarriages or preterm delivery) are not affected by conservative treatment.…”
Section: Obstetrics and Perinatal Outcomes After Conservative Treatme...mentioning
confidence: 99%
“…The treatments offered to patients can differ significantly based on the provisional diagnosis from imaging modalities, prior to a confirmative histological diagnosis [5]. Benign masses can be monitored without intervention, or, depending on their size and symptoms, a limited resection with a low peri-operative risk can be performed and may be beneficial for patients desiring fertility preservation [6][7][8]. It is known that findings of unilocular cysts in premenopausal women that measure less than 5 cm are associated with a less than 1% risk of malignancy, and these can be managed conservatively [9].…”
Section: Introductionmentioning
confidence: 99%